Searching new strategies for managing and controlling urban land growth: a preliminary outlook on Indonesia - Hadi Sabari Yunus (Faculty of Geography, Universitas Gadjah Mada, 1990)
This article is a result of an intensive study of literatures concerning urban growth management. It tries to examine the specific character of existing techniques for managing and controlling urban land growth and tries to match them to the Indonesian situation. The techniques can be categorized into two major types, i.e. urban and urral (urban-rural) orientation. Indonesian .urban sprawl can be distinguished into two models, i.e. the Java and Outer Islands model. Java model is characterized by leap-frog (see for example Jakarta, Bandung, Yogyakarta, Surakarta, Surabaya) and ribbon development (see for example Padang in Sumatra, Banjarmasin in Kalimantan, Kendari in Sulawesi). The physical, social, historical background are responsible for this conditions. The urban-rural oriented strategy is highly recommended for managing and controlling urban land growth on the island of Java whereas urban oriented techniques are suggested for managing and controlling urban land development on the outer islands.